Percutaneous endovascular arteriovenous fistula: A systematic review and meta-analysis - Sun, Ji-Bo; Liu, Chun-Cheng; Shen, Xi; Chen, Qin; Xu, Cheng-Liang; Cui, Tian-Lei (Frontiers in Cardiovascular Medicine, 2022)
Objective: Currently, percutaneous endovascular creation of arteriovenous fistula (AVF) shows excellent outcomes. However, few systematic research evidence to support clinical decision making on the benefit of endovascular AVF is available. The purpose of this study was to evaluate the efficacy and safety of endovascular AVF (endoAVF) in patients with renal failure. Methods: We searched the Medline, Embase, Cochrane Library, and Clinical Trials.gov databases for studies on endovascular or endovascular versus surgery for the creation of AVF. Two reviewers independently selected studies and extracted data. A systematic review and meta-analysis were performed by Review Manager 5.4 software (Revman, The Cochrane Collaboration, Oxford, UK) and Stata 15.0 (Stata Corp, College Station, TX, USA). Results: 14 case series and 5 cohort studies, with 1929 patients, were included in this study. The technique success was 98.00% for endoAVF (95% CI, 0.97-0.99; I2=16.25%). There was no statistically significant difference in 3 cohort studies between endovascular and surgical AVF for procedural success (OR = 0.69; 95% CI, 0.04-11.98; P = 0.80; I2=53%). The maturation rates of endoAVF were 87.00% (95% CI, 0.79-0.93; I2=83.96%), and no significant difference was observed in 3 cohort studies between the 2 groups (OR = 0.73; 95% CI, 0.20-2.63; P = 0.63; I2=88%). Procedure-related complications for endoAVF was 7% (95% CI, 0.04-0.17; I2=78.31%), and it did not show significant difference in 4 cohort studies between the 2 groups (OR = 1.85; 95% CI, 0.37-9.16; P = 0.45; I2=59%). Conclusions: The endovascular creation of AVF is potentially effective and safe. These important data may provide evidence to support clinicians and patients in making decisions with endovascular AVF. But further research is great necessary due to lack of randomized controlled studies.